BASIC MODERN METHODS OF THE PERINATAL DIAGNOSTICS OF THE HIP JOINT DYSPLASIA: WORLD TRENDS - Bilynskiy, Yosyp; Urvan, Olena; Guralnik, Artem (Scientific Works of Vinnytsia National Technical University, 2019)
The paper describes in details the modern methods of the comprehensive study of the congenital dysplasia of the hip joint in the antenatal and postnatal periods of infant development. Due to the application of modern technologies there appeared the possibility to visualize the initial changes not only in the osseous tissue but also in the soft tissues, which participate in the formation of the hip joint – cartilaginous tissue, muscles, ligaments, tendons, nervous tissue and vascular structures of the joint. Nowadays the state and density of the osseous tissue of the joint can already be determined in the antenatal period of the fetus development. Modern methods of the investigations enable to study in details and visualize tissues, forming the joint, to the finest details. Main task of the preventive diagnostics of the dysplasia is the decrease of the percentage of children, suffering from hip joint dysplasia (HJD), increase of the level of children health safety. Up to the present there existed two traditional methods of HJ study: clinical and roentgenologic. If clinical diagnostics of the hip dislocation is not very clear, then the detection of the subluxation and HJD in the infants of the first months of life causes certain difficulties. Leading role in the diagnostics of the disorders in the development of HJ is devoted to the roentgenologic method of investigation. However, the radiation dose, absorbed during such treatment does not allow to apply this method of study for the infants of less than three months of age. Besides, the nonostereogenic structures – parts of the femoral head, acetabular roof, which, in the infants of the first year life present greater part of these anatomic formations, are not represented in the X-ray image. As a result, it is impossible to detect the disorders of the enchondral formation, sometimes it is a leading manifestation of the hip joint dysplasia. Application of the method of the artificial contrast study of the joint is rather complicated and dangerous for the child. On the base of studying of various methods of HJD diagnostics ,which are scientifically substantiated and widely used in medical practice further development of basically new and improvement of the available diagnostic techniques, aimed at the solution of the problem of the hip joint dysplasia is possible.